Cochlear Implantation in Siblings With Refsum's Disease. (August 2017) - Stähr, Kerstin; Kuechler, Alma; Gencik, Martin; Arnolds, Judith; Dendy, Meaghan; Lang, Stephan; Arweiler-Harbeck, Diana
Objectives: Whether the origin of severe hearing loss in Refsum's syndrome is caused by cochlear impairment or retrocochlear degeneration remains unclear. This case report aims to investigate hearing performance before and after cochlear implantation to shed light on this question. Also, identification of new mutations causing Refsum's syndrome would be helpful in generating additional means of diagnosis. Methods: A family of 4 individuals was subjected to genetic testing. Two siblings (56 and 61 years old) suffered from severe hearing and vision loss and received bilateral cochlear implants. Genetic analysis, audiological outcome, and clinical examinations were performed. Results: One new mutation in the PHYH gene (c.768del63bp) causing Refsum's disease was found. Preoperative distortion product otoacoustic emissions (DPAOEs) were absent. Postoperative speech perception in Freiburger speech test was 100% for bisyllabic words and 85% (patient No. 1) and 65% (patient No. 2), respectively, for monosyllabic words. Five years after implantation, speech perception remained stable for bisyllabic words but showed decreasing capabilities for monosyllabic words. Discussion: A new mutation causing Refsum's disease is presented. Cochlear implantation in case of severe hearing loss leads to an improvement in speech perception and should be recommended for patients with Refsum's disease, especially when the hearing loss is combined with a severe loss of vision. Decrease of speech perception in the long-term follow-up could indicate an additional retrocochlear degeneration.